Construction of a lactate-related prognostic signature for predicting prognosis after surgical repair for acute type a aortic dissection - Wang, Zhigang; Li, Kai; Xu, Jingfang; Cheng, Xiaofeng; Wang, Dongjin (Frontiers in Physiology, 2022)
Abstract Background: Serum lactate is commonly measured in the perioperative period in patients who have undergone surgery for an acute type A aortic dissection (ATAAD). However, conflicting data has been reported as to whether lactate elevation is associated with short-term prognosis. The aim of the current study was to determine the association between perioperative arterial lactate levels and postoperative 30-day mortality. Methods: Patients who underwent repair of a ATAAD at our institution were retrospectively screened and those with comprehensive measurements of serum lactate before surgery and at 0, 1, 3, 6, 12, 24 h after surgery in the intensive care unit (ICU) were selected for the analysis. Patients’ demographic features and outcomes were reviewed to determine risk factors associated with 30-day mortality using logistic regression modeling. The association between serum lactate levels at different time points and 30-day mortality were analyzed by receiver-operating characteristic curves. Results: 513 patients were identified and retrospectively analyzed for this study including 66 patients (12.9%) who died within 30 days after surgery. Patients who died within 30 days after surgery had elevated lactate levels measured before surgery and at 0 h, 1 h, 3 h, 6 h, 12 h, and 24 h after their ICU stay. Lactate measured at 24 h post ICU admission (odds ratio, 2.131; 95% confidence interval, 1.346-3.374; p = 0.001) was a predictor of 30-day mortality. The area under the curve (AUC) for 30-day mortality with lactate levels at 12 h and 24 h post ICU stay were 0.820 and 0.805, respectively. Conclusion: Early elevation of lactate level is correlated with increased 30-day mortality in patients who received ATAAD surgical repair.